The influence of loads of various magnitudes and directions on the visual acuity of high-qualified visually impaired sprinters - Leilia Adzhametova; Liudmyla Shesterova (Kharkiv State Academy of Physical Culture, 2023)
Purpose: determine the impact of loads of different magnitudes and directions on the visual acuity of a highly qualified female athlete with visual impairments, specializing in sprinting. Material & methods. The study was conducted in the general preparatory period of the annual training cycle with the participation of the Honored Master of Sports of Ukraine in athletics among athletes with visual impairments. The following research methods were used: analysis of documentary materials (diaries and preparation plans of the studied athlete), pedagogical observation; Pedagogical experiment (author's experiment), visometry, methods of mathematical statistics. Results. It has been established that an increase in the load has a negative effect on visual acuity. The results obtained in the course of the study indicate a general trend in the response of both eyes to a load of a different nature. Conclusions. The use in the preparatory period of loads of a strength orientation, complex for endurance, coordination and flexibility, leads to an increase in visual acuity, which in turn has a positive effect on the functional state of the visual analyzer. Large loads aimed at speed endurance and having a speed-strength character lead to a decrease in visual acuity and, as a result, negatively affect the functional state of the visual analyzer.